Design : designul produselor din piele - Mihai, Aura, 1968-; Curteza, Antonela (Performantica, 2005)
"The design, a border and confluence field, captivating, fascinating, wonderful, innovative, and controversial, disputed, demanded or neglected, is unique and unmistakable. Related to fashion design, this wonderful creation of man who comes to complete the work of nature, the design seems to be more interesting and more inciting. Footwear and leather goods, considered fashion accessories are themselves products obtained through specific activities, carried out during the successive stages of a design process. Throughout the entire book - eng. Leather Products Fashion Design-, the authors have presented the concepts, the potential and the limitations regarding the different aspects of designing leather products. The design is analyzed as a process and as a product, under all its aspects: functional, structural and decorative. The physical attributes, the possibilities for aesthetic expression, the optical illusions and the emotional effects stimulated by the introduction of elements (line, form, colour, ornament) and the principles specific to design are explored."-- Anotace od dodavatele
Keywords: obuv; kožené výrobky; módní návrhářství; design; footwear; leather goods; fashion design; příručky; handbooks, manuals, etc